Discovery of a novel conformational equilibrium in urokinase-type plasminogen activator - Tobias Kromann-Hansen (Nature Portfolio, 2017)
Abstract Although trypsin-like serine proteases have flexible surface-exposed loops and are known to adopt higher and lower activity conformations, structural determinants for the different conformations have remained largely obscure. The trypsin-like serine protease, urokinase-type plasminogen activator (uPA), is central in tissue remodeling processes and also strongly implicated in tumor metastasis. We solved five X-ray crystal structures of murine uPA (muPA) in the absence and presence of allosteric molecules and/or substrate-like molecules. The structure of unbound muPA revealed an unsuspected non-chymotrypsin-like protease conformation in which two β-strands in the core of the protease domain undergoes a major antiparallel-to-parallel conformational transition. We next isolated two anti-muPA nanobodies; an active-site binding nanobody and an allosteric nanobody. Crystal structures of the muPA:nanobody complexes and hydrogen-deuterium exchange mass spectrometry revealed molecular insights about molecular factors controlling the antiparallel-to-parallel equilibrium in muPA. Together with muPA activity assays, the data provide valuable insights into regulatory mechanisms and conformational flexibility of uPA and trypsin-like serine proteases in general.